ISSUES OF CONSTITUTIONAL PROTECTION OF INDIVIDUAL RIGHTS TO EDUCATION IN UZBEKISTAN AND DEVELOPED COUNTRIES (World Bulletin of Management and Law, 2022)
Nowadays, in many countries, the practice of strengthening a number of important rights of the individual, in particular the right to education, is widely used in the constitutions, which are the highest guarantee of human and civil rights. If this practice first of all strengthens the right of a person to receive education from a legal point of view, then it creates a basis for improving the system of implementation of this right. In this article, the issues of constitutional protection of the right to education of the individual are analyzed on the basis of the constitutions of foreign countries.
Keywords: individual; education; constitutions; strengthens